2012
DOI: 10.2165/11599330-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Safety and Tolerability of Bencycloquidium Bromide, a Novel Selective Muscarinic M1/M3 Receptor Antagonist, After Single and Multiple Intranasal Doses in Healthy Chinese Subjects

Abstract: Background: Bencycloquidium bromide (BCQB) is a novel, potent and selective muscarinic M1/M3 receptor antagonist under development for the treatment of rhinorrhea in rhinitis. The pharmacokinetics and safety of BCQB in animals have been established in preclinical studies. However, no clinical pharmacokinetic data are available for BCQB in humans.Objective: The aim of this first-in-human study was to evaluate the pharmacokinetics, safety and tolerability of BCQB following single and multiple intranasal doses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A regression coefficient at a level of 0.1 was considered significant. This study used a predefined standard of (0.5, 2.0) 21,22 and a standard interval of (0.500, 1.500). Across the different dose groups, the relevant PK parameters were calculated using an analysis of variance (ANOVA) except for T max , which was calculated using a nonparametric test.…”
Section: Discussionmentioning
confidence: 99%
“…A regression coefficient at a level of 0.1 was considered significant. This study used a predefined standard of (0.5, 2.0) 21,22 and a standard interval of (0.500, 1.500). Across the different dose groups, the relevant PK parameters were calculated using an analysis of variance (ANOVA) except for T max , which was calculated using a nonparametric test.…”
Section: Discussionmentioning
confidence: 99%
“…24 In mice sensitized and challenged with ovalbumin to develop airway inflammation, inhalation administration of BCQB significantly reduced ovalbumininduced airway hyperresponsiveness and prevented the ovalbumin-induced increase in total cell counts and eosinophil counts. 25 An intranasal formulation of BCQB has been developed for the treatment of rhinorrhoea and is under clinical evaluation. BCQB proved to be safe and well tolerated in healthy Chinese subjects when administered intranasally with single and multiple doses across the doses studied.…”
Section: Bencycloquidiummentioning
confidence: 99%
“…Studies on general pharmacological actions of BCQB suggested that it had no obvious effect on cardiovascular and respiratory in beagle dogs, and could decrease the extraction of the bronchus gland and inhibit the peristalsis of the small intestine in mice [4,5]. Under the clinical trial, an early study has shown its tolerability and efficacy [6]. However, the investigations of drug interactions of BCQB in humans remain an important part of its safety.…”
Section: Introductionmentioning
confidence: 99%